Behavior pattern within the trading day based on trading hours on the Tehran Stock Exchange - Hamid Reza Raofi; Mohsen Mehrara (مدلسازی اقتصادسنجی, 2020)
The purpose of this paper was to model the intraday behavior of transactions based on trading hours on the Tehran Stock Exchange. For this purpose, statistical data extracted from Rahnavard Novin software have been used for the period of April 2009 to September 2017 based on the frequency of daily data. The variables used in this study include trading volume, return fluctuations, and differences between the best selling price. In this study, the time period for trading on the Tehran Stock Exchange is divided according to the time of 15 minutes. The volume of transactions and behavioral patterns for the first 3 15-minute intervals and the last 3 15-minute time intervals were examined. The results of this study showed that at the beginning and end of the market, the values ​​of value variables and trading volume and the values ​​of change and price increase increase, and the volume and size of transactions, unlike price changes and returns, are maximized at the end of the day. The results indicate that in fact the volume and value of transactions follow the pattern (J) of the shape and yield and price changes follow the pattern (L). Based on the results, the volume and value of transactions at the beginning and end of the day is higher than other times and at the end of the day the transaction is maximized.